Consequences of the marine climate and ecosystem shift of the 1980-90s on the Ligurian Sea biodiversity (NW Mediterranean). Issue 1 (1st January 2019) - Bianchi, C. N.; Azzola, A.; Bertolino, M.; Betti, F.; Bo, M.; Cattaneo-Vietti, R.; Cocito, S.; Montefalcone, M.; Morri, C.; Oprandi, A.; Peirano, A.; Bavestrello, G.
Abstract: A rapid temperature increase in the 1980-90s has been accompanied by dramatic and unprecedented changes in the biota and communities of the Ligurian Sea. This review uses existing historical series (a few of which have been purposely updated) to assess extent and consequences of such changes. A number of warm-water species, previously absent or occasional in the comparatively cold Ligurian Sea, has recently established thanks to warmer winters. Occurrence among them of invasive alien species is causing concern because of their capacity of outcompeting autochthonous species. Summer heatwaves, on the other hand, caused mass mortalities in marine organisms, some of which found refuge at depth. New marine diseases appeared, as well as other dysfunctions such as the formation of mucilage aggregates that suffocated and entangled benthic organisms. Human pressures have combined with climate change to cause phase shifts (i.e., abrupt variations in species composition and community structure) in different habitats, such as the pelagic environment, seagrass meadows, rocky reefs, and marine caves. These phase shifts implied biotic homogenization, reduction of diversity, and dominance by invasive aliens, and may be detrimental to the resilience of Ligurian Sea ecosystems. Another phase of rapid warming has possibly started in the 2010s and there are clues pointing to a further series of biological changes, but data are too scarce to date for proper assessment. Only well addressed long-term studies will help understanding the future dynamics of Ligurian Sea ecosystems and their possibilities of recovery.